Effect of sterilization of female and male rats on osteocyte cells - Dian Fatmawati; Irfan Idris; Dwi Kesuma Sari (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2021)
Sterilization is the recommended method of conception for animals. This method has also been used in many countries to control populations in dogs and cats. However, this action has some long-term effects as it affects the production of reproductive hormones in the body. This study aims to determine the effect of sterilization on the number of osteocytes. This study is an experimental study with a Posttest-Only Control Design, by observing rats that were fed standard feed until the age of 16 weeks and then terminated and measured the planned variables. A total of 24 rats aged 10 weeks were divided into 4 groups, namely 6 control females, 6 ovariohysterectomy females, 6 orchiectomy males, and 6 control males. 6 weeks after sterilization, all rats were euthanized and the left thigh bone was taken for histological examination of bone cells, namely osteocytic cells. The results of the analysis using the independent t-test, the results of the osteocyte cell test in females were p<0.05 which showed statistically that the sterilization action in female rats had a significant effect on the number of osteocyte cells, while in male rats, the value of p>0.05, which means statistically sterilization measures. had no significant effect on the number of osteocytes. Keywords: Ovariohisterectomy, Sterilization, Osteocytes Cells